International Community Service Report Improving Financial Literacy of Students at the At-Tanzil Learning Center (SB) -Elementary School Level, Malaysia - Lantow, Felmi D. (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
Financial literacy has gained global recognition as a crucial skill, emphasizing not only knowledge but also how it shapes attitudes and behaviors related to savings, spending, and avoiding consumptive habits. In Indonesia, policies on financial literacy focus on competence, prudent behavior, and access to financial services, with a growing emphasis on children and adolescents as key periods for habit formation. This community service activity aimed to foster financial literacy among elementary school students at SB At-Tanzil, Malaysia, by introducing concepts such as saving, prioritizing spending, and recording expenses through participatory and contextual methods. The activity included mentoring, simulations, group learning, games, and the use of piggy banks for savings practice, implemented over one session of 2–3 hours with 20 children aged 4–12. The results indicated that the children engaged positively, with many starting to save their allowances and making more thoughtful spending decisions. The activity succeeded in teaching them to distinguish between needs and wants and helped improve their ability to record savings. The program's success suggests that financial literacy should be a routine practice, with suggestions for incorporating a piggy bank project and a daily cash book to reinforce saving habits. Additionally, weekly parental checklists and regular assessments are recommended to ensure long-term progress and habit formation.